(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Keynote Address presented on the Occasion of the 2nd Faculty of Agriculture International Conference (Hybrid), Nnamdi Azikiwe University, Held at the University Auditorium, Awka Campus of the University from 12th to 14th March, 2024, during the Openning Ceremony Being Thursday 13th March, 2024